2016
DOI: 10.1097/md.0000000000002561
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating Lipoma of the Right Ventricle Involving the Interventricular Septum and Tricuspid Valve

Abstract: Cardiac lipoma, which are primary cardiac tumors, are rare entities often detected incidentally during imaging. There have been very few reports on the right ventricle (RV) lipoma. Here, we present a case of RV infiltrating lipoma involving the interventricular septum (IVS) and the tricuspid valve. Clinical symptoms, diagnostic procedures, multimodality imaging characteristics, and treatment are discussed, and the complete clinical data of this case and relevant details of retrospective literature are reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…Lipomas are benign encapsulated fatty lesions with unclear etiologies[ 1 ]. A study done by Italiano et al[ 9 ] showed that solitary lipoma is associated with chromosome 12 gene rearrangements, where an abnormality in HMGA2-LPP fusion gene was noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipomas are benign encapsulated fatty lesions with unclear etiologies[ 1 ]. A study done by Italiano et al[ 9 ] showed that solitary lipoma is associated with chromosome 12 gene rearrangements, where an abnormality in HMGA2-LPP fusion gene was noted.…”
Section: Discussionmentioning
confidence: 99%
“…LHIS, although has fatty deposits, it is a separate entity from lipoma with variable pathology[ 1 ]. Heyer et al[ 14 ] showed an LHIS incidence of 2.2% by multi-slice CT. Higher prevalence of LHIS has been observed in patients with advanced age, atrial arrhythmias, obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEE also confers the benefit of detecting small masses or unclear cardiac structures, especially when a transthoracic echocardiogram is suboptimal. [5]…”
Section: Discussionmentioning
confidence: 99%
“…[3] The right ventricle (RV) represents a very unusual location for cardiac lipomas with only a handful of these cases presented in the literature. [245] Herein, we report a case of a primary intracardiac lipoma of the RV which was attached to the interventricular septum (IVS).…”
Section: Introductionmentioning
confidence: 99%